2016
DOI: 10.3329/jdmc.v24i2.29615
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and Outcome of Acute Kidney Failure In Bangladeshi Children – Dhaka Medical College Hospital Experience

Abstract: Coll. 2015; 24(2) : 86-91.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The present study revealed pre renal risk factors (70.0%) were higher in percentage than renal (30.0%). This finding showed almost similarity with Afroz et al 11 where pre renal causes were 66.0% and renal causes were 32.0%. If we consider the risk factor of AKI in neonate separately, we found that all risk factors were pre renal.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study revealed pre renal risk factors (70.0%) were higher in percentage than renal (30.0%). This finding showed almost similarity with Afroz et al 11 where pre renal causes were 66.0% and renal causes were 32.0%. If we consider the risk factor of AKI in neonate separately, we found that all risk factors were pre renal.…”
Section: Discussionsupporting
confidence: 90%
“…In this study the male and female ratio is 2:1 in older age group which is almost matched with Afroz et al 11 where it is 1.9:1. The baseline creatinine has shown significant difference with non-AKI group, is similar to Safdar et al 4 .…”
Section: Discussionsupporting
confidence: 89%
“…Among renal causes nephrotoxic drug was the most important cause of AKI in this study. Afroz et al 12 found among renal causes 12.5% was drug induced. This showed no similarity with the finding of current study possibly due to different methodology.…”
Section: Discussionmentioning
confidence: 95%
“…Acute watery diarrhoea with severe dehydration was found as an important cause of AKI in Bangladesh. 18 Poor socioeconomic status, lack of food hygiene, poor hand washing before meal, lack of health education and public awareness is responsible for this in our country. 18 The mortality in AKI in children has been reported to vary widely from 16% to 43.8%.…”
Section: Study Limitations and Recommendationsmentioning
confidence: 99%
“…18 Poor socioeconomic status, lack of food hygiene, poor hand washing before meal, lack of health education and public awareness is responsible for this in our country. 18 The mortality in AKI in children has been reported to vary widely from 16% to 43.8%. 4,8,10 In the present study, mortality rate was 53 %, which is comparable to a recent study from Kuwait reporting 43.8 % mortality.…”
Section: Study Limitations and Recommendationsmentioning
confidence: 99%